2016
DOI: 10.3184/174751916x14579531034854
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal Structures of Two C24 Epimeric 3-Acetyled 20(R)-Ocotillol Type Sapogenins Obtained from 20(R)-Protopanaxadiol

Abstract: Two C24 epimeric 3-acetylated ocotillol-type sapogenins, 20 R,24 S-epoxy-dammarane-3β,12β,25-triol acetate and 20 R,24 R-epoxy-dammarane-3β,12β,25-triol acetate have been achieved from 20( R)-protopanaxadiol. Their structures were confirmed by HRMS, 1H NMR, 13C NMR and single crystal X-ray diffraction which showed that their configurations were (20 R, 24 S) and (20 R, 24 R), respectively. In the crystal structure of the 24 ( S)-epimer, there were two intramolecular hydrogen bonds and a left-handed helical chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The results indicated that the configurations of 31 and 32 were (20 R ,24 S ) and (20 R ,24 R ), respectively [34].…”
Section: Semisynthesis Of 20(r)-ocotillol-type Saponinsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results indicated that the configurations of 31 and 32 were (20 R ,24 S ) and (20 R ,24 R ), respectively [34].…”
Section: Semisynthesis Of 20(r)-ocotillol-type Saponinsmentioning
confidence: 97%
“…Two C24 epimeric 3-acetyled ocotillol-type sponins, (20 R ,24 S )-epoxy-dammarane-3β,12β,25-triol acetate ( M3 , 31 ) and (20 R ,24 R )-epoxy-dammarane-3β,12β,25-triol acetate ( M4 , 32; Table 3 ), were obtained from 20( R )-PPD, which made it possible to isolate 29 and 30 . The results indicated that the configurations of 31 and 32 were (20 R ,24 S ) and (20 R ,24 R ), respectively [34] .…”
Section: Semisynthesis Of 20( R )-Ocotillol-type Smentioning
confidence: 97%
“…Ginsenosides can be classifed as ocotillol-type, oleanolic acid type, protopanaxadiol (PPD) type, protopanaxatriol (PPT) type [5][6][7]. The ocotillol-type triterpenes are a rare kind of ginsenosides characterized by a tetrahydrofuran ring on the side chain [8][9][10][11]. It has been reported that ocotillol-type triterpenes have antibacterial, antioxidative, anti-inflammatory, neuroprotective and cardioprotective properties [12][13][14][15][16].…”
Section: Commentmentioning
confidence: 99%